2009
DOI: 10.1038/mp.2009.47
|View full text |Cite
|
Sign up to set email alerts
|

Increased excitotoxicity and neuroinflammatory markers in postmortem frontal cortex from bipolar disorder patients

Abstract: Reports of cognitive decline, symptom worsening and brain atrophy in bipolar disorder (BD) suggest that the disease progresses over time. The worsening neuropathology may involve excitotoxicity and neuroinflammation. We determined protein and mRNA levels of excitotoxicity and neuroinflammatory markers in postmortem frontal cortex from 10 BD patients and 10 age-matched controls. The brain tissue was matched for age, postmortem interval and pH. The results indicated statistically significant lower protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
306
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(322 citation statements)
references
References 52 publications
15
306
0
1
Order By: Relevance
“…The increased concentration of CSF IL-1β is in excellent agreement with a recent study showing increased mRNA levels of IL-1β in the postmortem brains of patients with bipolar disorder. 13 Given the similarities between schizophrenia and bipolar disorder, this finding is also in line with a recent study from our group showing increased concentration of this cytokine in the CSF of patients with a first-episode of schizophrenia. 2…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The increased concentration of CSF IL-1β is in excellent agreement with a recent study showing increased mRNA levels of IL-1β in the postmortem brains of patients with bipolar disorder. 13 Given the similarities between schizophrenia and bipolar disorder, this finding is also in line with a recent study from our group showing increased concentration of this cytokine in the CSF of patients with a first-episode of schizophrenia. 2…”
Section: Discussionsupporting
confidence: 79%
“…The increased concentration of CSF IL-1β is in excellent agreement with a recent study showing increased mRNA levels of IL-1β in the postmortem brains of patients with bipolar disorder. 13 Given the similarities between schizophrenia and bipolar disorder, this finding is also in line with a recent study from our group showing increased concentration of this cytokine in the CSF of patients with a first-episode of schizophrenia. 2 The presently observed aberrant CSF cytokine profile in euthymic patients with bipolar disorder (i.e., a selective activation of IL-1β concomitant with a reduction of IL-6) clearly differs from previous findings where cytokines of serum have been analyzed.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This was due to the fact that our search strategy was over-inclusive to avoid missing any suitable article. [24] Germany [28] Neuroinflammatory microglia activation is compatible with these data; the influence of medication has not been ruled out *S100β induces the expression of IL-1β in cultured ratmicroglia; [37,38] astrocyte synthesis of S100β in AD may be triggered by microglial-derived IL-1. [39] BA: brodmann's area; TNFR2: tumor necrosis factor receptor, type 2; IL-1β: interleukin-1 beta; MIP 1α/LD78: macrophage inflammatory protein-1 alpha/LD78; PrP c : cellular prion protein; QRT-PCR: quantitative real-time polymerase chain reaction; MyD88: myeloid differentiation factor 88; NF-κB: nuclear factor kappa B; GFAP: glial fibrillary acidic protein; iNOS: inducible nitric oxide synthase; NMDA: N-methyl-D-aspartic acid; HERV: human endogenous retrovirus; HERV-W: human endogenous retrovirus-W; AA: arachidonic acid; cPLA2: cytosolic phospholipase A2; sPLA2-IIA: secretory phospholipase A2-IIA; COX: cyclooxygenase; mPGES: membrane prostaglandin E synthase; cPGES: cytosolic prostaglandin E synthase; TNF-α: tumor necrosis factor α It proved to be more tiresome to download all papers, but this allowed us to identify two papers that would otherwise have gone undetected.…”
Section: Based On the Search Is There Any Evidence For Neuroinflammasupporting
confidence: 65%
“…It has been previously suggested that microglial cells might show reduced proliferation rates before BD onset, while cell degeneration might occur as a result of extensive inflammation due to microglia activation triggered by gliosis (Watkins et al, 2014). Additionally, histological brain analysis of frontal cortex samples showed an up-regulation of the pro-inflammatory and excitotoxicity-related proteins IL-1β, IL-1 receptor, iNOS and c-Fos suggesting that increased expression and activity rates of these might lead to cell death, brain atrophy and cognitive decline, as previously described for BD pathology (Rao et al, 2010). In the earlier stages of the disorder, interleukins and TNF-α are up-regulated while in later stages IL-6 and TNF-α levels expression are maintained (Rege and Hodgkinson, 2013).…”
Section: Molecular Basis Of Bipolar Disorder Progressionmentioning
confidence: 68%